Transformational leadership and performance: An experimental investigation of the mediating effects of basic needs satisfaction and work engagement. Issue 4 (18th June 2013) - Kovjanic, Snjezana; Schuh, Sebastian C.; Jonas, Klaus
Abstract : The aim of the present research was to integrate and extend theorizing on transformational leadership, self‐determination, and work engagement. Specifically, we tested experimentally our hypotheses that the satisfaction of followers' basic psychological needs (i.e., for competence, relatedness, and autonomy) and work engagement mediate the relationship between transformational leadership and performance. A total of 190 participants worked on a brainstorming task under either a transformational or a non‐transformational leadership condition. Followers' performance was operationalized through quantity, quality, and persistence. Results revealed that satisfaction of the needs for competence and relatedness mediated the relationship between transformational leadership and work engagement, which, in turn, was positively related to quality, quantity, and persistence. Taken together, these findings are largely in line with our theoretical model and support Bass' ( Leadership and performance beyond expectations . New York, NY: Free Press, 1985) and Burns' ( Leadership . New York: Harper & Row, 1978) theories on needs satisfaction being a central mechanism behind transformational leadership. Practitioner points: The results of this study suggest that organizations can benefit from implementing measures to increase employees' work engagement, because this can enhance employees' performance. Furthermore, the study provides an indication of how to design such measures. It suggests that initiatives focusing on followers' basic psychological needs satisfaction (especially of the needs for competence and relatedness) are particularly effective. Finally, our findings indicate that transformational leadership is one concrete way to foster employees' needs satisfaction and, consequently, work engagement and performance. Hence, integrating the frameworks of transformational leadership and followers' psychological needs can provide valuable insights for leadership development.